An abrasive water jet assisted back reaming technique based on percussion drilling for reducing non-production time in geothermal energy development. (January 2021) - Li, Yanliang; Peng, Jianming; Li, Keke; Bo, Kun; Wang, Maosen; Zhang, Pengyu
Highlights: An AWJ assisted back reaming technique based on percussion drilling is proposed. This technique can improve the reaming performance and efficiency. The optimal AWJ reaming parameters are obtained based on the premise of reducing non-production time. Percussion drilling provides a new way for efficient development of the geothermal wells. Abstract: Abrasive water jet (AWJ) technology is one of the fastest growing methods of cutting materials in recent years. Because percussion drilling can cause numerous impact cracks around the borehole, and these impact cracks can reduce the mechanical properties of the rock around the borehole. This makes it possible to improve AWJ reaming efficiency. The present paper investigates the influence of key jet parameters on AWJ reaming performance according to the specific problems encountered in the Gonghe geothermal well (GH-01). Additionally, the required time for AWJ reaming is analyzed and discussed. The results indicate that there is an existence of optimum value of jet standoff distance ( s/d0 = 3) for the AWJ reaming performance. Moreover, the high jet traverse speed will lead to deterioration of reaming performance. If the jet traverse speed is controlled under 50 mm/s, the slower the speed is, the better the reaming performance is. In the context of reaming a defined depth of rock, jet pressure has no significant effect on reaming performance. The requirement of reaming can be met by using jet pressure at 35 MPa. Although the effect of the inclined jet on penetration depth is better than that of the vertical jet, the vertical jet can produce a wider penetrate width. Compared with conventional reaming, the time spent on AWJ reaming is 55 %–67 % less than that of conventional reaming when the depth of reaming is 100 m. All the above merits have provided a theoretical foundation and experimental proof for the field application of the AWJ reaming technique.